Assessment of cholinesterase and tyrosinase inhibitory and antioxidant effects of Hypericum perforatum L. (St. John's wort) - Altun, M. Levent; Yilmaz, Betul Sever; Orhan, Ilkay Erdogan; Citoglu, Gulcin Saltan (Elsevier Science Bv, 2013)
In the current study, in vitro neuroprotective effect of the ethyl acetate, methanol, and water extracts of Hypericum perforatum L growing in Turkey was investigated through testing against acetylcholinesterase and butyrylcholinesterase at 50, 100, and 200 mu g mL(-1), linked to Alzheimer's disease, and tyrosinase at 250 mu g mL(-1), related to Parkinson's disease. As neurodegeneration is strongly correlated with oxidative damage and metal accumulation, antioxidant activity of the extracts was determined by radical scavenging assays against 2,2-diphenyl-1-picrylhydrazyl (DPPH), N,N-dimethyl-p-phenylendiamine (DMPD), super oxide, and nitric oxide radicals, as well as metal-chelation capacity, ferric- (FRAP), and phosphomolibdenum-reducing antioxidant power (PRAP). Total phenol and flavonoid quantities of the extracts were also determined. The methanol extract showed the highest acetylcholinesterase inhibition (49.54 +/- 4.44%), while the ethyl acetate extract had the best inhibition towards butyrylcholinesterase (50.79 +/- 3.07%). Only the methanol extract showed low tyrosinase inhibition (19.21 +/- 1.44%). In the antioxidant assays, the methanol extract had a greater activity in general. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Hypericum perforatum; St. John's wort; Hypericaceae; Cholinesterase; Tyrosinase; Antioxidant activity